CD25 expression on residual leukemic blasts at the time of allogeneic hematopoietic stem cell transplant predicts relapse in patients with acute myeloid leukemia without complete remission. Issue 6 (2nd June 2016) - Ikegawa, Shuntaro; Doki, Noriko; Kurosawa, Shuhei; Yamaguchi, Tsukasa; Sakaguchi, Masahiro; Harada, Kaito; Yamamoto, Keita; Hino, Yutaro; Shingai, Naoki; Senoo, Yasushi; Hattori, Keiichiro; Igarashi, Aiko; et al.
Abstract: Recent studies have shown that CD25 expression at the time of diagnosis of acute myeloid leukemia (AML) may be associated with an unfavorable outcome. We focus on patients with AML without complete remission (CR) and examine the clinical correlation between surface CD25 expression at the time of transplant and subsequent transplant outcomes. We observed a significant difference in overall survival (OS), disease-free survival (DFS) and cumulative incidence of relapse (CIR) between CD25 positive (+) ( n  = 22) and negative (−) groups ( n  = 44) (2-year OS; CD25 (+) group: 5% vs. CD25 (−) group: 40%, p  < 0.0001, 2-year DFS; 5% vs. 29%, p  < 0.0001, 2-year CIR; 77% vs. 52%, p  = 0.03). Multivariate analysis showed that CD25 expression was an independent adverse factor for OS ( p  = 0.002) and relapse ( p  = 0.001). Patients with AML with residual CD25 positive blasts at the time of transplant may require additional therapy before or after transplant to improve survival.